Efektifitas Bimbingan Kelompok Dengan Teknik Problem Solving Untuk Meningkatkan Percaya Diri Siswa - Ridho, Aisatur; Rahmawati, Weni Kurnia; Fauziyah, Nailul (Educatio, 2026)
This study aimed to examine the effectiveness of group guidance using a problem-solving technique in improving students’ self-confidence at Salafiyah Miftahul Huda Junior High School. The research applied a quantitative approach with a one-group pretest-posttest design. The participants were six eighth-grade students identified as having low self-confidence, selected purposively based on the results of a self-confidence scale. The instrument was a questionnaire consisting of 60 statements developed from Lauster’s indicators, which include self-belief, social interaction, and self-concept. The results revealed a significant increase in students’ self-confidence, with the mean score rising from 131.33 in the pretest to 272.00 in the posttest IV, with a significance value of p = 0.000 (<0.05). This improvement of approximately 107% was consistently reflected in all indicators. These findings confirm that group guidance with a problem-solving technique is effective in enhancing students’ self-confidence. Furthermore, the results provide practical implications for developing counseling services that are more targeted and responsive to students’ needs, both in academic and psychosocial contexts